PENGEMBANGAN e-LKPD BERBASIS PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI ASAM BASA - Shinta Nissa Mutia; M. Naswir; Isra Miharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine the process of developing e-LKPD based on Project Based Learning (PjBL) to improve students' critical thinking skills on acid-base materials, as well as to determine the feasibility and student response to the developed e-LKPD. This research uses the Lee & Owens development model. The research instruments used were interview guidelines and questionnaires. The developed product was validated by media experts and content experts, evaluated by chemistry teachers, and subsequently tested on a small group. The data analysis techniques used are qualitative data analysis and quantitative data analysis. Based on the results of media expert validation, the average score obtained was 4.53 with a